Pengaruh Trust (Kepercayaan) dan Online Shopping Experiences (Pengalaman Berbelanja Online) terhadap Perilaku Konsumen dalam Berbelanja Online: Prespektif Konsumen di Indonesia - Assegaff, Setiawan (Jurnal Aplikasi Manajemen, 2015)
The aim of this research is to investigate the relationship between trust and onlineshopping experience with people behavior in online shopping. The impact of these twodimensions (trust dan online shopping experience) would be explored in this study. Thisstudy applied Theory Planned of Behavior (TPB) and incorporates with two other dimensions.A research model was developed for this study. The research model consists of sixhypotheses that describe the relation between variables. Research and hypotheses was validatedby online survey that conducted in online shopping group in Indonesia and participatedby 215 respondents. Data collected from the survey was analyzed using StructuralEquation Model (SEM) with Smart PLS software. This research reveals that people in Indonesiawhile perform online shopping is affect by trust dimension, however online shoppingexperience dimension was found has no affect to people behavior in perform their next onlineshopping activity